The Relationship Between Husband's Support and Decision-Making Regarding IUD (Intra Uterine Device) Use - Hannumh, Rodiyah (Cattleya Darmaya Fortuna, 2025)
Many women experience difficulties in choosing a contraceptive method. This is not only due to the limited available methods, but also due to their lack of knowledge about the requirements and safety of these methods. Various factors must be considered, including health status, potential side effects, consequences of failure or unwanted pregnancy, planned family size, partner approval, and even cultural norms of the environment and parents. The purpose of this study was to determine the relationship between husband's support and the use of IUDs (Intra Uterine Devices) in the Bangunharjo hamlet, Bangunkerto, Turi, Sleman. This study used an analytical survey method with a cross-sectional time approach. The population in this study were all women of childbearing age at Posyandu Nusa Indah 1 and Posyandu Nusa Indah 2, totaling 65 people, and a sample of 31 people was obtained using a purposive sampling technique. The statistical test used was chi-square with the results read using Fischer's exact test, and the result was 0.059. In this study, the calculated p-value was greater than 0.05, so the hypothesis was rejected. Thus, it can be concluded that there is no relationship between husband's support and the decision to use an IUD (Intra Uterine Device) in Huraba I Village, Siabu District, Mandailing Natal Regency. Based on the research results and discussion, the author can provide suggestions to the PUS to increase information about IUDs so that the decision to use an IUD is based on the mother's health condition, not only based on the husband's wishes or because they are influenced by others.